AN ANALYSIS OF ILLOCUTIONARY ACT IN JOE BIDEN’S VICTORY SPEECH REGARDING UNITED STATES ELECTION - Zaenurdin Zaenurdin; Sri Supiah Cahyati (PROJECT (Professional Journal of English Education), 2024)
This research is an analysis of the Illocutionary act. It aimed to analyze the categories of the illocutionary act that used by Joe Biden’s speech, and what is dominant utterances used in his speech. This research applied the descriptive qualitative method and illocutionary at uses  act theory by Searle (1979). The data were taken from the The Washington Post, Friday, November 11, 2020, in Washington.. There were 59 utterances and the percentage of utterances were Expressive (42%), Assertive (24%), Commissive (19%), Declarative (10%), and Directive (5%). The result showed the dominant utterances used by Joe Bidens’ is Expresive (25 utterances), Biden showed his audiences an inner state in thanking, congratulating, and greeting. Based on the result, Joe Biden used low level in directive of illocutionary acts in his speech.